2016
DOI: 10.4162/nrp.2016.10.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary flavanones intake and lipid profiles according to the presence of metabolic syndrome in Korean women with type 2 diabetes mellitus

Abstract: BACKGROUND/OBJECTIVESThis study was aimed at examining the association between dietary flavanones intake and lipid profiles according to the presence of metabolic syndrome (MetS) in Korean women with type 2 diabetes mellitus (T2DM).SUBJECTS/METHODSA cross-sectional analysis was performed among 502 female T2DM patients (non-MetS group; n = 129, MetS group; n = 373) who were recruited from the Huh's Diabetes Clinic in Seoul, Korea between 2005 and 2011. The dietary intake was assessed by a validated semi-quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Fruits have plenty of nutrients and bioactive compounds, such as vitamins, minerals, antioxidants, phytochemicals, etc. Daily intake of flavanones was associated with lipid-lowering properties in type 2 diabetic patients with MetS [ 31 ]. According to the Tehran lipid glucose study, higher intake of red/purple fruits and vegetables (FVs) was related to lower body weight and abdominal fat gain after 3-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Fruits have plenty of nutrients and bioactive compounds, such as vitamins, minerals, antioxidants, phytochemicals, etc. Daily intake of flavanones was associated with lipid-lowering properties in type 2 diabetic patients with MetS [ 31 ]. According to the Tehran lipid glucose study, higher intake of red/purple fruits and vegetables (FVs) was related to lower body weight and abdominal fat gain after 3-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that a daily dose of 1000 mg of quercetin for 12 weeks was effective in alleviating PCOS features [ 61 ]. Moreover, previous studies have also indicated the potential effects of other flavonoids, such as resveratrol and soy isoflavones, in the treatment of PCOS through the regulation of steroidogenesis, metabolic parameters, ovarian cysts, and follicular development [ 62 , 63 , 64 ].…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…Whereas a higher total flavonoid intake was mostly related to lower TG levels [ 24 , 25 , 26 , 27 , 28 ], no associations were found with TC [ 26 , 27 ]. Evidence for flavonoid subclasses is also inconsistent [ 26 , 27 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%